2015
DOI: 10.1242/jcs.177493
|View full text |Cite
|
Sign up to set email alerts
|

PAK6 targets to cell-cell adhesions via its N-terminus in a Cdc42-dependent manner to drive epithelial colony escape

Abstract: The six serine/threonine kinases in the p21-activated kinase (PAK) family are important regulators of cell adhesion, motility and survival. PAK6, which is overexpressed in prostate cancer, was recently reported to localize to cell-cell adhesions and to drive epithelial cell colony escape. Here we report that PAK6 targeting to cell-cell adhesions occurs through its N-terminus, requiring both its Cdc42/ Rac interactive binding (CRIB) domain and an adjacent polybasic region for maximal targeting efficiency. We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 49 publications
(74 reference statements)
4
39
0
Order By: Relevance
“…Expression of PAK6 is targeted by miR-328 and miR-23a in prostate cancer cells (Liu et al, 2015; Cai et al, 2015), and by miR-429 in colon cancer cells (Tian et al, 2015). PAK6 interacts with the cell junction protein IQGAP1 in a kinase activity-dependent manner and regulates the dissociation of cell-cell junctions in growth factor-stimulated cells (Fram et al, 2014; Morse et al, 2016). PAK6 phosphorylates AR (Ser578 (Liu et al, 2013a), Ser308, Ser346, Ser360, Thr326 and Thr354 (Liu et al, 2013b), MDM2 (Thr158 and Ser186) (Liu et al, 2013a), and LIMK1 (Thr508) (Cai et al, 2015) in prostate cancer cells and is involved in cell growth and migration.…”
Section: Pak6 Biologymentioning
confidence: 99%
“…Expression of PAK6 is targeted by miR-328 and miR-23a in prostate cancer cells (Liu et al, 2015; Cai et al, 2015), and by miR-429 in colon cancer cells (Tian et al, 2015). PAK6 interacts with the cell junction protein IQGAP1 in a kinase activity-dependent manner and regulates the dissociation of cell-cell junctions in growth factor-stimulated cells (Fram et al, 2014; Morse et al, 2016). PAK6 phosphorylates AR (Ser578 (Liu et al, 2013a), Ser308, Ser346, Ser360, Thr326 and Thr354 (Liu et al, 2013b), MDM2 (Thr158 and Ser186) (Liu et al, 2013a), and LIMK1 (Thr508) (Cai et al, 2015) in prostate cancer cells and is involved in cell growth and migration.…”
Section: Pak6 Biologymentioning
confidence: 99%
“…In endothelial cells and C.elegans, p120 CTN may also dynamically modulate contractility at the lateral domains via its interaction with RhoA upstream regulators [65,66]. PAK family members, serine threonine kinases effectors of Rac1 and Cdc42 GTPase known to modulate contraction [67], could also participate: either via transiently activation by cell-cell contact formation (PAK1) [68] or localization at epithelial junctions (PAK4 and PAK6) [69][70][71][72].…”
Section: Thin Bundles and The Regulation Of Lateral Height And Junctimentioning
confidence: 99%
“…One of the studies has demonstrated that Cdc42 regulates the apical junction formation in human bronchial epithelial cells through PAK4 32 . PAK6, which was initially identified to be an androgen receptor protein, and has recently be reported to be involved in cell: cell dissociation in response to HGF, independent of androgen receptor (AR) signalling 33 and is thought to drive colony escape 34 .…”
Section: Introductionmentioning
confidence: 99%
“…In the study, PAK5 was shown to phosphorylate p120-catenin on Serine 288, but the effect of this interaction on the adherens junctions has not been assessed. Recent reports do suggest that GFP-tagged PAK5 can be localised to cell : cell junctions 34,37 , and it was suggested that PAK5 might regulate junctional integrity, however neither study considered bladder cancer cells. This study aims to establish the expression profile of PAK family proteins in bladder cancer samples and elucidate whether PAK5 plays a specific functional role in bladder cancer cells.…”
Section: Introductionmentioning
confidence: 99%